EFEKTIVITAS PEMANFAATAN BANTARAN TUKAD BADUNG SEBAGAI RUANG TERBUKA PUBLIK DI KOTA DENPASAR - I Gusti Made Ananda Putra; I Gusti Putu Anindya Putra; I Nyoman Harry Juliarthana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
The city of Denpasar has made a new public open space arrangement by utilizing the existing space, in the form of the arrangement of the Tukad Badung riverbank at Kumbasari Park in Denpasar City. The activities carried out are recreation and as a forum for interaction for the community. Because of the phenomenon of using the Tukad Badung riverbank as a forum for interaction and community activities, it is therefore important to see the level of effectiveness and the dominant factors used in measuring the effectiveness of using the Tukad Badung bank as an open space public. The effectiveness of good utilization of public open space can be seen from the characteristics of space users and the characteristics of activities as an approach. The research data were obtained through observation, questionnaires, interviews, documentation, and agency surveys. Data analysis used qualitative descriptive analysis techniques with the Good Public Space Index method approach. The results showed the level of effectiveness of the use of the Tukad Badung riverbank as a public open space in Denpasar City at a value of 0.70 which is included in the "high" category. This assessment is obtained based on the results of the average value of the six indexes of the Good Public Space Index method. The dominant factors to measure the effectiveness of the use of the Tukad Badung riverbank as a public open space, namely the six GPSI indexes. The highest factor is the people's duration of stay index with a value of 0.88 or very high, it can be said that the Tukad Badung riverbank is very effective in accommodating the utilization of the diversity of time duration carried out by visitors in activities on the banks of Tukad Badung, on the contrary the intensity of use shows value of 0.45 and intensity of social use with a value of 0.60. This shows that the effectiveness of the Tukad Badung riverbank as a public open space in accommodating the large number of visitors and community groups who are included in the "medium" category due to the dominance of the number of people significant at a time.